NILAI HARAPAN ATAS LAYANAN JAMINAN KESEHATAN DI BANDAR LAMPUNG - Aswin - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
Services of public health insurance is a program initiated by the central and local governments toprovide health insurance to the poor.The programs initiated are not only limited to the fulfillment ofthe government's performance, but it can meet the expectations of the people who are less able toget health insurance in accordance with the standards of decent treatment. The results of a researchshowed that there is negative gap between the performance of hospitals and health centers and thehope of patients on health insurance services. The results of each dimension of service quality, theaverage values obtained overall dimensions of quality (Q) is 0.767 <1, it indicates that the quality ofservice perceived by the patient / community use of health care services is still not well or notoptimal, so not able to meet the expectations of patients .